2016
DOI: 10.1073/pnas.1600564113
|View full text |Cite
|
Sign up to set email alerts
|

Novel DLK-independent neuronal regeneration in Caenorhabditis elegans shares links with activity-dependent ectopic outgrowth

Abstract: During development, a neuron transitions from a state of rapid growth to a stable morphology, and neurons within the adult mammalian CNS lose their ability to effectively regenerate in response to injury. Here, we identify a novel form of neuronal regeneration, which is remarkably independent of DLK-1/DLK, KGB-1/JNK, and other MAPK signaling factors known to mediate regeneration in Caenorhabditis elegans, Drosophila, and mammals. This DLK-independent regeneration in C. elegans has direct genetic and molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
67
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 71 publications
5
67
0
1
Order By: Relevance
“…Regrowth responses diminish distally from the soma. Some chemosensory dendrites exhibit regenerative responses after dendrite injury (dendrotomy) (Wu et al 2007); moreover, a recent report suggests that dendrotomy alters the axonal response to injury in ASJ neurons (Chung et al 2016) (see below).…”
Section: Axon Regeneration After Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Regrowth responses diminish distally from the soma. Some chemosensory dendrites exhibit regenerative responses after dendrite injury (dendrotomy) (Wu et al 2007); moreover, a recent report suggests that dendrotomy alters the axonal response to injury in ASJ neurons (Chung et al 2016) (see below).…”
Section: Axon Regeneration After Injurymentioning
confidence: 99%
“…However, in neurons such as ALM, dlk-1 null mutants display partial regrowth after axotomy, indicating the existence of DLK-1-independent regrowth pathways. Moreover, axotomized chemosensory neurons such as ASJ display regenerative regrowth in response to dendrotomy that is independent of the DLK-1 and KGB-1/JNK cascades (Chung et al 2016). In these neurons, inhibition of neuronal activity by a variety of methods, including mutation of Ca 2+ channels, altered membrane potential, or sensory transduction, can promote DLK-1-independent regeneration after axotomy.…”
Section: Other Pathways Regulating Axon Regenerationmentioning
confidence: 99%
“…Mutation of dlk-1 also eliminated regeneration after laser cutting of ASJ axons. Surprisingly, however, Chung et al (5) found that simultaneous cutting of the ASJ axon and dendrite restores the regenerative capacity of ASJ axons even in dlk-1 mutants. Thus, dendrite lesion appears to activate a novel type of Dlkindependent axon regrowth.…”
mentioning
confidence: 94%
“…The effect of the preconditioning lesion has been thought to result from the first lesion driving neuronal de-differentiation and resetting its fate to something more like a developing neuron (4), but the precise mechanisms involved have remained unclear. In PNAS, Chung et al (5) use an elegant combination of genetics, laser ablations, and pharmacology to demonstrate that dendrites actively repress regenerative outgrowth in functionally mature neurons through a pathway that is independent of the well-conserved dual leucine zipper kinase (DLK)-regulated regeneration cascade (Fig. 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation